Harvesting change: Tech-driven solutions for paddy residue management - Singh, Rajbir; Jha, S. N. (Indian Farming, 2025)
The management of paddy residue in northwest India, particularly Punjab, Haryana, and Uttar Pradesh, constitutes a critical environmental and agricultural challenge owing to large-scale residue burning, which causes severe air pollution, soil degradation, and health risks. To address this, a range of farm machineries, such as the Super SMS attachment, Happy Seeder, Smart Seeder, Surface Seeder and Super Seeder, have revolutionized in in situ rice residue management practices. Supported by robust government schemes and extensive Information, Education, and Communication (IEC) initiatives led by Krishi Vigyan Kendras, these mechanized solutions have resulted in an impressive reduction of residue burning incidents between 2020 and 2024. A detailed economic evaluation highlights the cost-effectiveness and ecological sustainability of these methods compared to conventional burning. Short-duration rice varieties and crop diversification serve as pivotal strategic interventions to effectively reduce residue generation. The integration of technological innovation, robust policy frameworks, and heightened farmer awareness collectively paves a transformative pathway towards sustainable conservation agriculture, promoting enhanced productivity, environmental stewardship, and the long-term resilience of the rice-wheat cropping system in this crucial agrarian region.